Ed Ricketts' Lab exhibit. - Vinnie Lopez:::Photographer::::::::::::; Steven Domingo:::Photographer:::::::::::: (Monterey, California, 2023)
Ed Ricketts' Lab exhibit found in the Pacific Biological Laboratory building on Cannery Row.